Kajian Potensi Lahan Milik Rakyat Dalam Menghasilkan Kayu Di Kecamatan Kare Kabupaten Madiun - Setyo Martono, Djoko; Rahayu, Sri (JURNAL AGRI-TEK, 2014)
The results obtained from the timber land owned by people of unknown magnitude in Java , it is important to know because the alleged amount is not little , except to meet the needs , planting timber on land owned by the people also to preserve the environment , resist erosion and improve soil fertility , as long as wise people keep cutting down the tree without exceeding the existing increment and with regard to the principles of conservation . The purpose of this research is to determine the extent of a timber from the land belongs to the people in the district of Madiun Kare .The experiment was conducted on land owned by the District Rural Randualas Kare Kuwiran and Madison County in September to October 2013.Metode used in this research is descriptive quantitative method , the method of sampling wearing a multistage sampling technique with unequal size .The results showed that the production potential of community forest management varies depending on the shape of the plant and the type of crops grown on his land . Average timber potential of the people in the District of Kare at 94.2843 m3 / ha , with an average of Hamlet Dawung greatest potential with the average potential 121.4745 m3/ha and the average potential in the smallest village to the average Kuwiran average potential 58.7810 m3/ha . While the estimated average annual increment of 12.6830 m3 / ha / year.Keywords : Potential , Land Owned , Wood